Detection of novel non-M2-related antimitochondrial antibodies in patients with anti-M2 negative primary biliary cirrhosis. Issue 7 (30th March 2009) - Feuchtinger, M; Christ, S; Preuß, B; Dengjel, J; Duman, S; Stevanovic, S; Klein, R
Abstract : Objective: In 95% of patients with primary biliary cirrhosis (PBC) antimitochondrial antibodies (AMAs) can be detected reacting with at least one of the five components of the M2 antigen identified as the 2-oxoacid dehydrogenase complex (OADC). However, among our PBC sera 15–20% are anti-M2 negative by ELISA and western blotting but in the immunofluorescence test (IFT) they show the typical AMA staining. The aim of the present study was to characterise the target antigen(s) of these non-M2-related AMAs. Patients and methods: We analysed sera from 27 patients with clinically and histologically proven PBC being AMA positive by the IFT but anti-M2 negative by ELISA and western blotting. They were tested by western blotting against various 100 000  g supernatants obtained after sonication of mitochondria from rat liver, bovine heart and pig kidney. These were further separated by isopycnic sucrose density centrifugation using different sucrose density fractions. Results: Fourteen of the 27 AMA positive/anti-M2 negative sera (52%) reacted in the western blotting with a 60 kDa protein and eight (29%) with an 80 kDa protein, both present in the 100 000  g supernatant from bovine heart mitochondria accumulating at sucrose densities of 1.14–1.16. An identity of these determinants with any of the M2-related antigens could be excluded. In the 60 kDa band components of the mitochondrial enzymes F1 F0 -ATPase, ubiquinone cytochrome c reductase and acyl CoA dehydrogenase were detected by MALDI–TOF analysis; the 80 kDa protein could not be further characterised. Conclusions: AMA positive/anti-M2 negative PBC sera contain antibodies to further mitochondrial antigens at 60 and 80 kDa which do not correspond to any of the M2 determinants. Those antibodies can be detected to a lesser extent in sera from patients with classical anti-M2 positive PBC but not in patients with other hepatic and non-hepatic disorders and may, therefore, represent additional marker antibodies for the serological diagnosis of PBC.